1998
DOI: 10.1046/j.1365-2672.1998.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the preservative properties of Thymus vulgaris essential oil in topically applied formulations under a challenge test

Abstract: The preservative properties of thyme essential oil (3%) with a known composition were evaluated in two types of final formulations, suitable for use as pharmaceutical or cosmetic vehicles, by means of a standard challenge test proposed by the latest European Pharmacopoeia. The required preservation efficacy criteria were satisfied against the bacterial strains, against the yeast in one of the formulations, but not against the mould strain involved in this study. Interactions between the essential oil compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(103 citation statements)
references
References 4 publications
2
91
0
4
Order By: Relevance
“…Considering the antimicrobial activity reported for this plant species, a preservative action from this extract, when incorporated to a gel, could be equally expected, as it has been reported for other species (Nostro, 2002;Manou, 1998).…”
Section: Introductionmentioning
confidence: 66%
“…Considering the antimicrobial activity reported for this plant species, a preservative action from this extract, when incorporated to a gel, could be equally expected, as it has been reported for other species (Nostro, 2002;Manou, 1998).…”
Section: Introductionmentioning
confidence: 66%
“…Methane was the predominant gas, indicating that these chemicals are not bactericidal to the methanogenic population. Previous studies have suggested that a combination of both oils would provide better antimicrobial action rather than a higher concentration of carvacrol or thymol alone [6,8]. Other parameters (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…An example of a natural preservative agent is carvacrol, which is present in the essential oil fraction of oregano (60 -74%, v/v carvacrol) and thyme (45%, v/v carvacrol) [11]. Thyme also contains a significant amount of thymol (38%) [6], which is an equally effective antimicrobial chemical [2,15]. These plant-derived oils are generally recognized as safe (GRAS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several monoterpenes are widely used in the agriculture, cosmetic, and food industries, and as a general antiseptic in medical practice (Aeschbach et al, 1994;Lee et al, 1997;Manou et al, 1998). Most of the aroma from citrus fruit oil, cherries, and mint is due to the high content of monoterpenes, but they have no nutritional value because they are exclusively vegetable (Serrano et al,2006).…”
Section: Introductionmentioning
confidence: 99%